Confronting the Dark Matter of Higher Education: Building Trust in Pedagogical Relationships - Bloom-Christen, Anna; Kelland, Lindsay; Tabensky, Pedro (Critical Studies in Teaching and Learning, 2025)
This paper explores the structural and ideological constraints that militate against the trust required between teachers and students for effective teaching and learning in contemporary South African universities and beyond. The first part of the paper addresses how widespread commercialisation and precarity born of scarcity, in addition to other widely explored issues relating to the legacy of apartheid and colonisation in South Africa, foster distrust between teachers and students in the South African academy. The second part opens with an inquiry into the meaning and power of trust, before bringing this inquiry to bear on the higher education context and presenting recommendations for fostering trust and meaningful connections in academic settings based on our own experiences teaching a student-led course in ethics at Rhodes University in South Africa, named ‘IiNtetho zoBomi’ or ‘Conversations About Life.’